Digital Document Management Application Web and Android Based - Diana Diana; Ashadi Putra (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2021)
The development of technology has an impact on the way documents are managed. Documents that are stored manually in paper form become digital documents. Digitalization aims to save documents as an effort to maintain accessibility so that documents can be stored in a longer lasting form. Digital documents employed in the application are documents contained in the Informatics Engineering study program, Muhammadiyah University of Bengkulu by means of scanning. The digital document management application developed using the web and Android is to minimize technical problems when the application is implemented because the data recorded both on the web and on Android are integrated with each other. Testing of the application used the black box method and questionnaire. The test results indicate that the application is free from syntax errors and is functionally successful and has a "very good" aspect of usability value with a value of 4.36